S-doped g-C3N4 / Bi2MoO6Z type heterojunction photocatalyst as well as preparation method and application thereof
By doping sulfur atoms into g-C3N4 in the Bi2MoO6-based composite catalyst, the S-doped g-C3N4/Bi2MoO6 Z-type heterojunction structure is formed, which solves the problem of easy recombination of photogenerated electrons and holes, and significantly improves photocatalysis Efficiency achieves the effect of efficient degradation of organic pollutants.
Patent Information
- Application Number
- CN202411584475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The photogenerated electrons and holes of the traditional Bi2MoO6-based composite catalyst are easily recombined, resulting in low photocatalytic efficiency.
By doping sulfur atoms into g-C3N4, an S-doped g-C3N4/Bi2MoO6 Z-type heterojunction structure is formed, which reduces the separation efficiency of photogenerated electrons and holes, and adjusts the light absorption performance through the heterojunction structure.
The photocatalytic efficiency of the photocatalyst is significantly improved, and the degradation efficiency of 20 mg·L-1 rhodamine B is greater than 99.9% in 50 minutes.
Smart Images

Figure HDA0005123965770000011 
Figure HDA0005123965770000012 
Figure HDA0005123965770000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis and relates to an S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] As an effective means to solve the energy crisis and environmental pollution, photocatalysis technology has attracted the attention of a large number of researchers. The development of cheap, efficient, environmentally friendly photocatalysts with a wide spectral response range has become the core direction of photocatalysis research. As a typical Bi-based semiconductor photocatalyst, bismuth molybdate is widely used in photocatalytic energy conversion and pollutant control due to its non-toxicity, low cost, corrosion resistance and stability in chemical and optical properties.
[0003] However, the energy band structure of traditional bismuth molybdate materials limits their photocatalytic performance, making it difficult to achieve both wide spectral response and good redox ability, significantly reducing their photocatalytic activity. In addition, the photogenerated electrons and holes in Bi2MoO6 are very easy to recombine, further reducing its photocatalytic efficiency. In contrast, g-C3N4, as a layered photocatalytic material, has a medium-width band gap electronic structure. Its excellent thermal stability, chemical stability and non-toxicity have attracted widespread attention. However, pure g-C3N4 has defects such as small specific surface area, high charge recombination rate and low visible light utilization efficiency, which limits its potential in photocatalytic applications. The existing technology combines g-C3N4 with Bi2MoO6 to prepare a composite material, which effectively improves the photocatalytic degradation performance of the material, but the current process is relatively complicated and cannot be industrialized and mass-produced, and the catalytic efficiency also needs to be further improved. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst and a preparation method and application thereof, thereby solving the technical problems in the prior art that the photogenerated electron-hole recombination rate of Bi2MoO6-based composite catalysts is high and the photocatalytic efficiency is low.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst comprises the following steps:
[0007] S1: Grinding melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then subjecting the powder to a thermal polycondensation reaction to obtain sulfur-doped g-C3N4;
[0008] S2: adding sulfur-doped g-C3N4 to anhydrous ethanol, performing a first stirring, then adding a mixed solution of a molybdenum source and a bismuth source, performing a second stirring, and obtaining a suspension; the first stirring time is 20 to 50 minutes, and the second stirring time is 3 to 7 hours;
[0009] S3: performing solvent thermal treatment on the suspension to obtain the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst.
[0010] Preferably, the mass ratio of melamine to ammonium bromide is (1-2):(1-2), and the mass of thioacetamide accounts for 1% to 5% of the mass of melamine.
[0011] Preferably, in step S1, the temperature of the thermal polycondensation reaction is 500-560° C., and the time is 2-4 hours.
[0012] Preferably, the mixed solution of the molybdenum source and the bismuth source is prepared by adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source and stirring.
[0013] Preferably, in the ethylene glycol solution of the molybdenum source, the ratio of the molybdenum source to ethylene glycol is (1-4) mmol:20 mL; in the ethylene glycol solution of the bismuth source, the ratio of the bismuth source to ethylene glycol is (1-5) mmol:20 mL.
[0014] Preferably, the mass of the sulfur-doped g-C3N4 added is 10% to 40% of the theoretical yield of Bi2MoO6, and the molar ratio of the molybdenum source to the bismuth source is (1 to 3):(1 to 3).
[0015] Preferably, during the solvent thermal treatment process, the temperature is 150-200° C. and the time is 4-7 hours.
[0016] Preferably, after the solvent thermal treatment, the obtained product is further washed, dried and ground. During the drying process, the temperature is 60 to 90° C. and the drying time is 6 to 12 hours.
[0017] A S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst is prepared by the above method, wherein the S-doped g-C3N4 in the heterojunction catalyst is a porous sheet structure, the Bi2MoO6 is a nanorod structure, and the S-doped g-C3N4 and Bi2MoO6 are interlaced to form a Z-type heterojunction structure; the specific surface area of the heterojunction photocatalyst is 35 to 40 m 2 ·g -1 , aperture 0.2~0.4cm 3 ·g -1 ; Under visible light, within 50min, for 20mg·L -1The degradation efficiency of Rhodamine B was greater than 99.9%.
[0018] The above-mentioned S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst is used in the photocatalytic degradation of organic pollutants.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The invention discloses a method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst. The invention prepares a heterojunction material with a Z-type structure by simple mixing and grinding, thermal polycondensation reaction and solvent thermal reaction. First, S replaces N in the g-C3N4 lattice by thermal polycondensation reaction. The radius of the S atom is slightly larger than the radius of the nitrogen atom, which is conducive to interlayer peeling and the increase of the surface area, and increases the number of reactive active sites. Then, the S-doped g-C3N4 / Bi2MoO6 is subjected to solvent thermal reaction to form a Z-type heterojunction structure with Bi2MoO6. The Z-type heterojunction structure effectively reduces the separation efficiency of photogenerated electrons and holes, and promotes the photocatalytic efficiency. In addition, the light absorption performance of the material is adjusted by the formation of the heterojunction, and the catalytic performance of the material under visible light is improved. Therefore, the method of the invention is simple, the design is reasonable, and the recombination rate of photogenerated electrons and holes in the Bi2MoO6-based composite catalyst is effectively reduced, and the photocatalytic efficiency of the material is improved.
[0021] Further, the mass ratio of melamine to ammonium bromide is (1-2): (1-2), the mass of thioacetamide accounts for 1%-5% of the mass of melamine, melamine is a precursor for preparing g-C3N4, and ammonium bromide acts as a co-catalyst or template agent, affecting the morphology and structure of g-C3N4. When the mass ratio of melamine to ammonium bromide is controlled within the range of (1-2): (1-2), the pore structure and specific surface area of g-C3N4 can be optimized, thereby providing more reactive sites. The presence of ammonium bromide also promotes the doping process of sulfur atoms in thioacetamide in the g-C3N4 lattice, improving doping efficiency and doping uniformity. When thioacetamide is used as a sulfur source and its mass accounts for 1%-5% of the mass of melamine, it can ensure that an appropriate amount of sulfur atoms are doped into g-C3N4. Too little sulfur doping cannot significantly affect the performance of the material, while too much sulfur doping leads to the destruction of the material structure or performance degradation. Appropriate amount of sulfur doping can adjust the band structure of g-C3N4, making it more suitable for photocatalytic reactions.
[0022] Further, in step S1, the temperature of the thermal polycondensation reaction is 500-560°C, and the time is 2-4h. The temperature of the thermal polycondensation reaction is a key factor affecting the raw material conversion rate and the product structure. The temperature range of 500-560°C can ensure that raw materials such as melamine, ammonium bromide and thioacetamide are fully reacted to form a stable g-C3N4 structure and achieve effective doping of sulfur atoms. Within this temperature range, the crystal structure of g-C3N4 can be optimized to form more pores and a larger specific surface area, which is conducive to providing more reactive sites and improving photocatalytic performance; the appropriate temperature can also promote the diffusion and doping process of sulfur atoms in thioacetamide in the g-C3N4 lattice, ensuring that sulfur atoms can be evenly distributed in g-C3N4 to form a stable sulfur-doped g-C3N4 structure. The time of the thermal polycondensation reaction is an important factor affecting the quality and performance of the product. The reaction time of 2-4h can ensure the full reaction between the raw materials, form a high-quality g-C3N4 structure, and achieve effective doping of sulfur atoms. Too long a reaction time can lead to the destruction of the g-C3N4 structure or excessive doping of sulfur atoms, thus affecting the photocatalytic performance. A reaction time of 2 to 4 h can avoid this and ensure the stability and performance of the product.
[0023] Furthermore, the preparation process of the mixed solution of the molybdenum source and the bismuth source is to add the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source and stir to obtain; in the ethylene glycol solution of the molybdenum source, the amount ratio of the molybdenum source to the ethylene glycol is (1-4) mmol: 20mL; in the ethylene glycol solution of the bismuth source, the amount ratio of the bismuth source to the ethylene glycol is (1-5) mmol: 20mL, and the dropwise addition method can ensure that the molybdenum source solution is evenly dispersed in the bismuth source solution, avoiding the local concentration that may be too high or too low due to direct mixing, thereby ensuring the uniformity and consistency of the reaction. By precisely controlling the amount of the molybdenum source and the bismuth source, the composition of the final product can be precisely regulated, which helps to obtain products with specific chemical compositions and properties to meet different application requirements.
[0024] Furthermore, the mass of the sulfur-doped g-C3N4 added is 10% to 40% of the theoretical output of Bi2MoO6, and the molar ratio of the molybdenum source to the bismuth source is (1 to 3): (1 to 3). When the amount of sulfur-doped g-C3N4 added is within the range of 10% to 40% of the theoretical output of Bi2MoO6, a good and stable Z-type heterojunction structure can be formed, which helps to effectively separate photogenerated electrons and holes, thereby improving the photocatalytic efficiency. The appropriate amount of sulfur-doped g-C3N4 and Bi2MoO6 can be combined to broaden the light absorption range and improve the utilization efficiency of light energy. At the same time, the Z-type heterojunction structure helps to retain strong oxidation and reduction capabilities, further improving the photocatalytic performance. By adjusting the amount of sulfur-doped g-C3N4 added, the chemical composition, band structure and surface properties of the composite material can be regulated, thereby optimizing its photocatalytic performance and other related properties. The molar ratio of the molybdenum source to the bismuth source is controlled within the range of (1-3):(1-3), which can ensure that the stoichiometric ratio of the final product Bi2MoO6 is close to the theoretical value, thereby obtaining a product with high purity and crystallinity. The appropriate molar ratio of the molybdenum source to the bismuth source helps promote the growth of Bi2MoO6 crystals and form a product with regular morphology and structure. This helps to improve the photocatalytic performance and other physical properties of the product.
[0025] Furthermore, during the solvent heat treatment process, the temperature is 150-200°C and the time is 4-7h. Within this temperature range, the activity of the solvent is enhanced, which helps the solute to dissolve and disperse in the solvent. For solutes that need to improve solubility, appropriate temperature is one of the key factors. Temperature is an important factor affecting the rate of chemical reactions. Within this temperature range, the activation energy of the reactants is reduced and the reaction rate is accelerated, which helps the reaction and the generation of products. Excessive temperature leads to the occurrence of side reactions, affecting the purity and performance of the products, while within this temperature range, the reaction process can be better controlled to reduce the generation of by-products. Sufficient time can ensure sufficient contact and reaction between the reactants, thereby generating more target products. For systems that require long-term reactions, it is necessary to appropriately extend the reaction time. As the reaction time increases, the crystallinity and purity of the product will also be improved.
[0026] Furthermore, after the solvent heat treatment, the obtained product is also washed, dried and ground. During the drying process, the temperature is 60 to 90°C and the drying time is 6 to 12 hours. Within the temperature range of 60 to 90°C, the solvent in the product can be effectively removed, while avoiding excessively high temperatures that cause changes in the product structure or degradation of performance. Appropriate drying temperature helps to maintain the chemical stability and physical properties of the product and prevent unnecessary chemical reactions or structural changes during the drying process. Within this temperature range, the drying efficiency is high, and the drying time can be shortened, thereby reducing production costs. At the same time, the appropriate temperature can also ensure the uniformity of the drying process and avoid uneven drying inside the product. A drying time of 6 to 12 hours can ensure that the solvent in the product is completely removed, thereby avoiding the influence of residual solvent on product performance. Appropriate drying time helps to maintain the quality and performance of the product and prevents product structure damage or performance degradation caused by excessively long drying time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 XRD (a) and FT-IR (b) spectra of the 10% = Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 1 of the present invention;
[0029] Figure 2 XRD (a) and FT-IR (b) spectra of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 2 of the present invention;
[0030] Figure 3 XRD (a) and FT-IR (b) spectra of the 10% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 3 of the present invention;
[0031] Figure 4 The SEM images (a, b) at different magnification ratios, the full XPS spectrum (c) and the XPS spectrum of the S element (d) of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 2 of the present invention;
[0032] Figure 5The BET test results of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst and pure g-C3N4 prepared in Example 2 of the present invention, wherein (a) is a specific surface area spectrum of pure g-C3N4 and 20% Sg-C3N4 / Bi2MoO6 composite heterojunction, and (b) is a pore size spectrum of pure g-C3N4 and 20% Sg-C3N4 / Bi2MoO6 composite heterojunction;
[0033] Figure 6 A comparison chart of the degradation effects of 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 2 of the present invention and pure g-C3N4 on Rhodamine B under visible light;
[0034] Figure 7 The electron capture experiment of the main active material of 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst;
[0035] Figure 8 The UV absorption (a) and Mott-Schottky (MS) analysis curve (b) of 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst;
[0036] Fig. 9 This is a diagram of the free radical generation mechanism of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in the present invention. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0038] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0039] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0040] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0041] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0042] The present invention provides a method for preparing an S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst, comprising the following steps:
[0043] S1: Grinding melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then calcining at 500-560° C. for 2-4 hours to obtain sulfur-doped g-C3N4;
[0044] The mass ratio of melamine to ammonium bromide is (1-2):(1-2), and the mass of thioacetamide accounts for 1%-5% of the mass of melamine.
[0045] S2: adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source, stirring to obtain a mixed solution of the molybdenum source and the bismuth source; adding the sulfur-doped g-C3N4 into anhydrous ethanol, performing a first stirring, and then adding the mixed solution of the molybdenum source and the bismuth source, performing a second stirring to obtain a suspension; the first stirring time is 20 to 50 minutes, preferably 30 minutes, and the second stirring time is 3 to 7 hours, preferably 4 hours;
[0046] In the ethylene glycol solution of the molybdenum source, the ratio of the molybdenum source to ethylene glycol is (1-4) mmol:20 mL, and the ratio is preferably 1 mmol:20 mL. The molybdenum source is added to the ethylene glycol and stirred for 30-60 minutes to form a clear solution to obtain the ethylene glycol solution of the molybdenum source;
[0047] In the ethylene glycol solution of the bismuth source, the ratio of the bismuth source to ethylene glycol is (1-5) mmol:20 mL, and the ratio is preferably 1 mmol:20 mL. The bismuth source is added to the ethylene glycol and stirred for 30-60 minutes to form a clear solution, thereby obtaining the ethylene glycol solution of the bismuth source;
[0048] The mass of the sulfur-doped g-C3N4 added is 10% to 40% of the theoretical yield of Bi2MoO6 generated by the reaction of the molybdenum source and the bismuth source, and the molar ratio of the molybdenum source to the bismuth source is (1 to 3): (1 to 3).
[0049] In addition, the bismuth source is bismuth nitrate pentahydrate, and the molybdenum source is molybdenum nitrate dihydrate.
[0050] S3: Solvent thermal treatment is performed on the suspension at 100-200°C for 4-7h, and the obtained material is cooled to room temperature, centrifuged and washed in sequence, and dried at 60-90°C for 6-12h. After grinding, the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst is obtained. In the solvent thermal treatment process, the temperature is more preferably 120-180°C, more preferably 140-180°C, more preferably 160°C, and the time is preferably 5h. The drying temperature is more preferably 70-85°C, more preferably 70-80°C, and the time is preferably 6-10h, more preferably 7-9h, and more preferably 8h.
[0051] The present invention relates to a method for preparing an S-doped g-C3N4 / Bi2MoO6 composite material, forming a Z-type heterojunction photocatalyst, and belongs to the field of photocatalysis technology. The preparation method specifically comprises the following steps:
[0052] Mixing and grinding: Mix and grind melamine, ammonium bromide and thioacetamide to obtain a uniform mixed powder.
[0053] Thermal polycondensation reaction: The mixed powder is subjected to a thermal polycondensation reaction to obtain sulfur-doped g-C3N4.
[0054] Preparation of suspension: The obtained S-doped g-C3N4 is mixed with bismuth nitrate and molybdenum nitrate solutions to form a suspension.
[0055] Solvothermal reaction: The suspension was subjected to a solvothermal reaction to obtain a heteroatom-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst.
[0056] The present invention adopts a thermal polycondensation method and a solvent thermal method, and can obtain Z-type heterojunction samples with different contents and types by accurately controlling the doping amount in the reaction. The preparation process has the advantages of being simple and easy to operate, rich in product variety, low in cost, strong in operation repeatability and high in yield.
[0057] The prepared S-doped g-C3N4 has a porous lamellar structure, while bismuth molybdate has a nanorod structure. The formed S-doped g-C3N4 / Bi2MoO6 (abbreviated as S-PCN / Bi2MoO6) is a nano-microspherical heterojunction catalyst in which the two are interlaced and tightly combined.
[0058] The catalyst prepared by the method of the present invention exhibits excellent visible light photocatalytic activity, can significantly degrade organic pollutants, and has broad application prospects in the fields of energy utilization and environmental pollutant treatment.
[0059] In addition, the present invention also discloses a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst prepared by the above method, wherein the catalyst reduces the band gap by doping heterogeneous S elements to expand the light response range, wherein S replaces N in the g-C3N4 lattice, and the radius of the S atom is slightly larger than the radius of the nitrogen atom, which is conducive to interlayer peeling and surface area increase. The heterogeneous structure greatly increases the specific surface area, and at the same time obtains more reactive active sites, thereby having better photocatalytic performance.
[0060] The S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst of the present invention is prepared by the above method. In the heterojunction catalyst, the S-doped g-C3N4 is a porous sheet structure, the Bi2MoO6 is a nanorod structure, and the S-doped g-C3N4 and Bi2MoO6 are interlaced to form a Z-type heterojunction structure; the specific surface area of the heterojunction photocatalyst is 35 to 40 m 2 ·g -1 , aperture 0.2~0.4cm 3 ·g -1 ; Under visible light, within 50min, for 20mg·L -1 The degradation efficiency of Rhodamine B was greater than 99.9%.
[0061] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0062] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0063] Example 1
[0064] 4g of melamine, 4g of ammonium bromide and 0.12g of thioacetamide were put into an agate mortar and ground thoroughly for 30 minutes until mixed to obtain a mixed powder. Subsequently, the mixed powder was transferred to a muffle furnace and calcined at a high temperature of 550°C (the product was named 3S-PCN). After cooling, the obtained material was ground evenly, and 0.12g of the sample was dissolved in anhydrous ethanol and stirred to form a uniform suspension for standby use. Next, 2mmol of bismuth nitrate pentahydrate and 1mmol of sodium molybdate dihydrate were dissolved in 20mL of ethylene glycol, stirred for 30min, and bismuth nitrate solution and sodium molybdate solution were obtained; sodium molybdate solution was added dropwise to bismuth nitrate solution, stirred for 30min, and a mixed solution was obtained; the mixed solution was added to the above-mentioned suspension of anhydrous ethanol, stirred for 4 hours, and a final suspension was obtained, which was transferred to a reactor and subjected to a solvent thermal reaction at 160°C for 5 hours. After the reaction, the material was cooled to room temperature, centrifuged, and washed three times with distilled water and anhydrous ethanol. Finally, the obtained sample was dried at 80°C for 8 hours and then ground evenly to obtain the final photocatalyst. The product was named 10% Sg-C3N4 / Bi2MoO6, that is, S-doped g-C3N4 accounted for 10% of the theoretical yield of Bi2MoO6, and the mass of thioacetamide accounted for 3% of the mass of melamine.
[0065] Figure 1 The XRD (a) and FT-IR (b) spectra of the 10% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in this example are shown in FIG. Figure 1 (a) It can be seen that diffraction peaks appear at 10.9, 28.3, 32.5, 47.2 and 55.5°, which correspond to the (020), (131), (002), (062) and (133) planes of Bi2MoO6, respectively, while 13.0° and 27.6° correspond to the (100) and (002) diffraction planes of g-C3N4. Due to the low doping amount of 3S-PCN and the 27.6° diffraction peak being close to the 28.3° diffraction peak of Bi2MoO6, it is not obvious. Figure 1 (b) It can be seen that 552cm -1 and 705cm -1 The two absorption peaks at 1615-1225cm are the Bi-O deformation vibration and Mo-O stretching vibration signal peaks. -1 It is the stretching vibration peak of CN. This shows that in the characterization spectrum, not only the stretching vibration peak and diffraction peak belonging to S-doped g-C3N4 but also the stretching vibration peak and diffraction peak of Bi2MoO6 were observed, proving the successful construction of the heterojunction.
[0066] Example 2
[0067] The difference from Example 1 is that S-doped g-C3N4 accounts for 20% of the theoretical yield of Bi2MoO6, and the product is named 20% Sg-C3N4 / Bi2MoO6, that is, S-doped g-C3N4 accounts for 20% of the theoretical yield of Bi2MoO6, of which the mass of thioacetamide accounts for 3% of the mass of melamine.
[0068] Figure 2 XRD (a) and FT-IR (b) spectra of the 20% Sg-C3N4 / Bi2MoO6 composite material prepared in Example 2 of the present invention. Figure 2 (a) It can be seen that diffraction peaks appear at 10.9, 28.3, 32.5, 47.2 and 55.5°, which correspond to the (020), (131), (002), (062) and (133) planes, respectively, which is the same as Example 1. In addition, 13.0° and 27.6° correspond to the (100) and (002) diffraction planes of g-C3N4. With the increase of 3S-PCN content, the diffraction peak at 13.0° gradually increases. Figure 2 (b) It can be clearly seen that its infrared spectrum analysis is similar to that of Example 1.
[0069] Example 3
[0070] The difference from Example 1 is that S-doped g-C3N4 accounts for 30% of the theoretical yield of Bi2MoO6, and the product is named 30% Sg-C3N4 / Bi2MoO6, that is, S-doped g-C3N4 accounts for 30% of the theoretical yield of Bi2MoO6, of which the mass of thioacetamide accounts for 3% of the mass of melamine.
[0071] Figure 3 The XRD (a) and FT-IR (b) spectra of the 30% Sg-C3N4 / Bi2MoO6 composite material prepared in Example 3 of the present invention are the same as in Example 1. It can be clearly seen that diffraction peaks appear at 10.9, 28.3, 32.5, 47.2 and 55.5°, which correspond to the (020), (131), (002), (062) and (133) planes respectively; and 13.0° and 27.6° correspond to the (100) and (002) diffraction planes of g-C3N4. With the increase of 3S-PCN content, the diffraction peak at 13.0° gradually increases. Its infrared spectrum analysis is similar to that of Example 1.
[0072] Figure 4 The SEM images (a, b) at different magnifications, the full XPS spectrum (c) and the XPS spectrum of the S element (d) of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in Example 2 of the present invention are shown in FIG. Figure 4(a, b) show that the prepared S-doped g-C3N4 presents a lamellar porous structure, Bi2MoO6 is a nanorod-like structure, and the Sg-C3N4 / Bi2MoO6 composite material is composed of nanorod-like Bi2MoO6 and nanosheet-like S-doped g-C3N4 interpenetrating and stacking to form a nanosphere. Figure 4 (c, d) It can be seen that C, N, O, S, Mo, and Bi elements were successfully introduced, especially the successful doping of S element.
[0073] Figure 5 These are the BET test results of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst and pure g-C3N4 prepared in Example 2 of the present invention, wherein (a) is the specific surface area spectrum of pure g-C3N4 and 20% Sg-C3N4 / Bi2MoO6 composite heterojunction, and (b) is the pore size spectrum of pure g-C3N4 and 20% Sg-C3N4 / Bi2MoO6 composite heterojunction; it can be seen from the figure that the specific surface area and pore volume of the modified catalyst are greatly improved compared with pure g-C3N4.
[0074] In order to study the photocatalytic performance of the heterojunction photocatalyst prepared in the present invention, an experiment of photocatalytic degradation of Rhodamine B was carried out under visible light using the catalyst prepared in Example 2.
[0075] The reaction process is as follows: 0.05 g of the catalyst prepared in Example 2 is dissolved in 100 ml of a 20 mg / L rhodamine B solution, stirred for 30 min in a dark environment, a 300 W xenon lamp is used as the light source, and a UV filter is used to filter out light below 420 nm. 3 mL of the reaction solution is drawn at regular intervals, and after filtration, the concentration of rhodamine B in the reaction solution is determined by a UV-visible spectrophotometer, and the test results are compared with those of pure g-C3N4. The test results are shown in Figure 6 ,As can be seen from the figure, the construction of the heterojunction effectively improves the photocatalytic performance of the photocatalyst, and 99% of the Rhodamine B solution can be degraded within 50 minutes.
[0076] Figure 7 This is the electron capture experiment of the main active material of 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst. (a) is the photodegradation test under the same conditions, with isopropyl alcohol (IPA), disodium oxalate tetraacetate (EDTA-2Na) and p-benzoquinone (p-BQ) added as ·OH, h + and O2 -sacrificial agent. Compared with the group without scavenger, only 35% of RhB was degraded after adding p-benzoquinone, while the degradation efficiency was reduced to 49.1% after adding isopropanol. Similarly, the addition of EDTA-2Na also reduced the photocatalytic efficiency, indicating that h+ affects the degradation of RhB. In addition, ESR tests were performed on it, as shown in (B), (C) and (D), and the studies were conducted under light and dark conditions, respectively. It can be seen that under dark conditions, no DMPO-·O2 was observed in the photocatalyst. - The signal peaks of DMPO-·OH and DMPO-·OH confirm that no·O2 is produced under light-free conditions - and ·OH. However, ·O2 - and ·OH, indicating that ·O2 - and ·OH can be generated and participate in the photocatalytic degradation process. And ·O2 - Play a major role.
[0077] Figure 8 The UV absorption and Mott-Schottky (MS) analysis curves of the 20% Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst. From (a), we can see that the band gap values Eg of 3S-PCN and BM are 2.45 and 2.78 eV respectively. From the MS curve of (b), we can calculate Eg. CB,3S-PCN and E CB,BM -0.43V and -0.31V respectively.
[0078] Fig. 9 The diagram is a diagram of the free radical generation mechanism of the Sg-C3N4 / Bi2MoO6 composite heterojunction catalyst prepared in the present invention. As can be seen from the figure, based on the results obtained, the band-to-band transfer mechanism of the composite material and the process of degrading RhB are proposed. Figure 7 When 3S-PCN (i.e. Sg-C3N4 prepared in the present invention) and BM (i.e. Bi2MoO6) are interface-coupled, the CB and VB potentials of BM are higher than the edge potentials of 3S-PCN, which may be a type II heterojunction or a Z-type heterojunction.
[0079] Under the irradiation of visible light, if the charge separation mechanism between 3S-PCN and BM belongs to type II heterojunction, then the photogenerated electrons on the conduction band of 3S-PCN will be preferentially transferred to the conduction band of BM, while h + However, since the CB potential of BM (-0.31 eV) is lower than that of O2 / ·O2 - (-0.33eV) is corrected, resulting in the inability of photogenerated electrons in the BM conduction band to effectively react with O2. The VB potential of 3S-PCN (2.02eV) is lower than that of OH - / ·OH (1.99 eV) is positive, but more negative than H2O / ·OH (2.38 eV), so that the photogenerated holes in the valence band of 3S-PCN cannot oxidize H2O to ·OH. This is contrary to the results of capture experiments and EPR tests (such as Figure 7 Therefore, type II heterojunction charge transfer is not possible in this system.
[0080] If a Z-type heterojunction is formed between BM and 3S-PCN, that is, under the irradiation of visible light, electrons will be excited from the valence band of BM to its conduction band, leaving positively charged hole ions in the valence band. Then, the electrons in the conduction band of BM will migrate to the valence band of 3S-PCN and be further excited to the conduction band of 3S-PCN, finally achieving effective separation of carriers. In this case, since the VB potential of BM (2.47 eV) is more positive than that of H2O / ·OH, it will be conducive to the formation of hydroxyl radicals. The CB potential of 3S-PCN (-0.43 eV) is more positive than that of O2 / ·O2 - The potential is more negative, and the electrons can also react with O2 in the air to generate O2 - This can explain the O2 - The generation of ·OH and ·OH is consistent with the test results. Therefore, it can be inferred that the charge transfer mechanism of 3S-PCN and BM is a Z-type heterostructure, which effectively promotes charge separation and thus achieves efficient degradation of target pollutants.
[0081] The present invention first synthesizes porous S-doped g-C3N4 through element doping, and the synergistic effect of the nanosheet structure and S doping enhances the absorption of visible light and increases the specific surface area, thereby providing more reaction sites and effectively separating and transferring photogenerated charges. Subsequently, a hydrothermal method is used to composite it with Bi2MoO6 to construct a heterojunction. During the hydrothermal process, a certain amount of anhydrous ethanol is added thereto, thereby reducing the reaction temperature required in the reaction process, and also reducing the reaction time and the occurrence of dangerous accidents. The heterojunction catalyst finally synthesized has a greatly increased specific surface area and pore size relative to pure g-C3N4. During the preparation process of the S-doped g-C3N4, the band gap is reduced by adding a heterogeneous S element, thereby expanding the light response range. S replaces N in the g-C3N4 lattice, and the radius of the S atom is slightly larger than that of the nitrogen atom, which is conducive to interlayer peeling and the increase of the surface area. The heterostructure construction greatly increases the specific surface area, and more reactive sites are obtained, thereby having good photocatalytic performance.
[0082] Example 4
[0083] A method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst comprises the following steps:
[0084] S1: Grinding melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then calcining at 500°C for 4h to obtain sulfur-doped g-C3N4;
[0085] The mass ratio of melamine to ammonium bromide is 1:2, and the mass of thioacetamide accounts for 1% of the mass of melamine.
[0086] S2: adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source, stirring to obtain a mixed solution of the molybdenum source and the bismuth source; adding the sulfur-doped g-C3N4 into anhydrous ethanol, performing a first stirring, and then adding the mixed solution of the molybdenum source and the bismuth source, performing a second stirring to obtain a suspension; the first stirring time is 20 minutes, and the second stirring time is 3 hours;
[0087] In the ethylene glycol solution of the molybdenum source, the molybdenum source and ethylene glycol are used in a ratio of 1 mmol:20 mL, the molybdenum source is added to the ethylene glycol, and stirred for 30 min to form a clear solution, thereby obtaining the ethylene glycol solution of the molybdenum source;
[0088] In the ethylene glycol solution of the bismuth source, the ratio of the bismuth source to ethylene glycol is 1 mmol:20 mL, the bismuth source is added to the ethylene glycol, and stirred for 30 minutes to form a clear solution, thereby obtaining the ethylene glycol solution of the bismuth source;
[0089] The mass of the sulfur-doped g-C3N4 added is 10% of the theoretical yield of Bi2MoO6 generated by the reaction of the molybdenum source and the bismuth source, and the molar ratio of the molybdenum source to the bismuth source is 1:1.
[0090] In addition, the bismuth source is bismuth nitrate pentahydrate, and the molybdenum source is molybdenum nitrate dihydrate.
[0091] S3: The suspension was subjected to solvent thermal treatment at 150°C for 7 hours. The obtained material was cooled to room temperature, centrifuged and washed in sequence, and dried at 60°C for 12 hours. After grinding, the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst was obtained.
[0092] The specific surface area of the heterojunction photocatalyst prepared in this embodiment is 35m 2 ·g -1 , aperture 0.2cm 3 ·g -1 ; Under visible light, within 50min, for 20mg·L -1 The degradation efficiency of Rhodamine B was 99.9%.
[0093] Example 5
[0094] A method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst comprises the following steps:
[0095] S1: Grind melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then calcine at 560°C for 2h to obtain sulfur-doped g-C3N4;
[0096] The mass ratio of melamine to ammonium bromide is 2:1, and the mass of thioacetamide accounts for 5% of the mass of melamine.
[0097] S2: adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source, stirring to obtain a mixed solution of the molybdenum source and the bismuth source; adding the sulfur-doped g-C3N4 into anhydrous ethanol, performing a first stirring, and then adding the mixed solution of the molybdenum source and the bismuth source, performing a second stirring to obtain a suspension; the first stirring time is 50 minutes, and the second stirring time is 3 hours;
[0098] In the ethylene glycol solution of the molybdenum source, the molybdenum source and ethylene glycol are used in a ratio of 4 mmol:20 mL, the molybdenum source is added to the ethylene glycol, and stirred for 60 min to form a clear solution, thereby obtaining the ethylene glycol solution of the molybdenum source;
[0099] In the ethylene glycol solution of the bismuth source, the ratio of the bismuth source to ethylene glycol is 5 mmol:20 mL, the bismuth source is added to the ethylene glycol, and stirred for 60 minutes to form a clear solution, thereby obtaining the ethylene glycol solution of the bismuth source;
[0100] The mass of the sulfur-doped g-C3N4 added is 40% of the theoretical yield of Bi2MoO6 generated by the reaction of the molybdenum source and the bismuth source, and the molar ratio of the molybdenum source to the bismuth source is 2:1.
[0101] In addition, the bismuth source is bismuth nitrate pentahydrate, and the molybdenum source is molybdenum nitrate dihydrate.
[0102] S3: The suspension was subjected to solvent thermal treatment at 200°C for 4 hours. After the obtained material was cooled to room temperature, it was centrifuged and washed in sequence, and dried at 90°C for 6 hours. After grinding, the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst was obtained.
[0103] The specific surface area of the heterojunction photocatalyst prepared in this embodiment is 40 m 2 ·g -1 , aperture 0.2cm 3 ·g -1 ; Under visible light, within 50min, for 20mg·L -1 The degradation efficiency of Rhodamine B was 99.9%.
[0104] Example 6
[0105] A method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst comprises the following steps:
[0106] S1: Grind melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then calcine at 530 ° C for 2 h to obtain sulfur-doped g-C3N4;
[0107] The mass ratio of melamine to ammonium bromide is 1:1.5, and the mass of thioacetamide accounts for 2% of the mass of melamine.
[0108] S2: adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source, stirring to obtain a mixed solution of the molybdenum source and the bismuth source; adding the sulfur-doped g-C3N4 into anhydrous ethanol, performing a first stirring, and then adding the mixed solution of the molybdenum source and the bismuth source, performing a second stirring to obtain a suspension; the first stirring time is 30 minutes, and the second stirring time is 4 hours;
[0109] In the ethylene glycol solution of the molybdenum source, the molybdenum source and ethylene glycol are used in a ratio of 1 mmol:20 mL, the molybdenum source is added to the ethylene glycol, and stirred for 40 minutes to form a clear solution, thereby obtaining the ethylene glycol solution of the molybdenum source;
[0110] In the ethylene glycol solution of the bismuth source, the ratio of the bismuth source to ethylene glycol is 2 mmol:20 mL, the bismuth source is added to the ethylene glycol, and stirred for 40 minutes to form a clear solution, thereby obtaining the ethylene glycol solution of the bismuth source;
[0111] The mass of the sulfur-doped g-C3N4 added is 20% of the theoretical yield of Bi2MoO6 generated by the reaction of the molybdenum source and the bismuth source, and the molar ratio of the molybdenum source to the bismuth source is 1:2.
[0112] In addition, the bismuth source is bismuth nitrate pentahydrate, and the molybdenum source is molybdenum nitrate dihydrate.
[0113] S3: The suspension was subjected to solvent thermal treatment at 160°C for 5 hours. The obtained material was cooled to room temperature, centrifuged and washed in sequence, and dried at 80°C for 9 hours. After grinding, the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst was obtained.
[0114] The specific surface area of the heterojunction photocatalyst prepared in this embodiment is 41m 2 ·g -1 , aperture 0.2cm 3 ·g - 1; Under visible light, within 50min, for 20mg·L -1 The degradation efficiency of Rhodamine B was 99.99%.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst, characterized in that: The following steps are involved: S1: Grinding melamine, ammonium bromide and thioacetamide solids to obtain a uniform mixed powder, and then subjecting the powder to a thermal polycondensation reaction to obtain sulfur-doped g-C3N4; S2: adding sulfur-doped g-C3N4 to anhydrous ethanol, performing a first stirring, then adding a mixed solution of a molybdenum source and a bismuth source, performing a second stirring, and obtaining a suspension; the first stirring time is 20 to 50 minutes, and the second stirring time is 3 to 7 hours; S3: performing solvent thermal treatment on the suspension to obtain the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst.
2. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: The mass ratio of melamine to ammonium bromide is (1-2):(1-2), and the mass of thioacetamide accounts for 1%-5% of the mass of melamine.
3. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: In step S1, the temperature of the thermal polycondensation reaction is 500-560° C., and the time is 2-4 hours.
4. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: The mixed solution of the molybdenum source and the bismuth source is prepared by adding the ethylene glycol solution of the molybdenum source dropwise into the ethylene glycol solution of the bismuth source and stirring.
5. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 4, characterized in that: In the ethylene glycol solution of the molybdenum source, the usage ratio of the molybdenum source to ethylene glycol is (1-4) mmol:20 mL; in the ethylene glycol solution of the bismuth source, the usage ratio of the bismuth source to ethylene glycol is (1-5) mmol:20 mL.
6. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: The mass of the sulfur-doped g-C3N4 added is 10% to 40% of the theoretical yield of Bi2MoO6, and the molar ratio of the molybdenum source to the bismuth source is (1 to 3): (1 to 3).
7. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: During the solvent thermal treatment process, the temperature is 150-200° C. and the time is 4-7 hours.
8. The method for preparing a S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst according to claim 1, characterized in that: After the solvent thermal treatment, the obtained product is washed, dried and ground. During the drying process, the temperature is 60 to 90° C. and the drying time is 6 to 12 hours.
9. A S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 8, wherein the S-doped g-C3N4 is a porous sheet structure, the Bi2MoO6 is a nanorod structure, and the S-doped g-C3N4 and Bi2MoO6 are interlaced to form a Z-type heterojunction structure; the specific surface area of the heterojunction photocatalyst is 35 to 40 m 2 ·g -1 , aperture 0.2~0.4cm 3 ·g -1 ; Under visible light, within 50min, for 20mg·L -1 The degradation efficiency of Rhodamine B was greater than 99.9%.
10. Use of the S-doped g-C3N4 / Bi2MoO6 Z-type heterojunction photocatalyst as claimed in claim 9 in photocatalytic degradation of organic pollutants.
Citation Information
Patent Citations
Graphite-phase carbon nitride (g-C3N4) material and preparation method and application thereof
CN105126893A
Nano Ag modified WO3-g-C3N4 Z-type heterojunction photocatalyst and preparation method thereof
CN112044463A
Preparation method of phosphorus-doped graphite phase carbon nitride / bismuth molybdate heterojunction
CN114082436A
Preparation method and application of ball-flower-shaped Bi2WO6 loaded sulfur-doped porous carbon nitride composite photocatalyst
CN118002174A